Review of Aluminum-To-Steel Welding Technologies for Car-Body Applications - Alessio Gullino; Paolo Matteis; Fabio D’Aiuto (Metals, 2019)
Hybrid car bodies fabricated by joining parts made with steel and aluminum alloys are becoming increasingly common. This provides an affordable mean to decrease the car weight by using lighter or more advanced materials only where they can achieve the maximum benefit. This development is driven mainly by recent regulations on carbon dioxide emissions, and hinges on the deployment of effective joining technologies. In most cases, such technologies were not previously used in the car sector, and must be adapted to its requirements. Several dissimilar welding technologies, based on either fusion welding or solid-state welding, are reviewed here, focusing on dissimilar joining among steels and wrought aluminum alloys. These technologies are either presently being introduced in the car industry, or are used in other sectors and could be applied in the car industry in the near future.